PERFORMANCE OF EVACUATED TUBE SOLAR COLLECTOR USING WATER-BASED TITANIUM OXIDE NANOFLUID - M. Mahendran; G.C. Lee; K.V. Sharma; A. Shahrani; R.A. Bakar (Journal of Mechanical Engineering and Sciences, 2012)
Experiments are undertaken to determine the efficiency of an evacuated tube solar collector using water-based Titanium Oxide (TiO2) nanofluid at the Pekan Campus (3˚32’ N, 103˚25’ E), Faculty of Mechanical Engineering, University Malaysia Pahang, for the conversion of solar thermal energy. Malaysia lies in the equatorial zone with an average daily solar insolation of more than 900 W/m², which can reach a maximum of 1200 W/m² for most of the year. Traditionally water is pumped through the collector at an optimum flow rate, for the extraction of solar thermal energy. If the outlet temperature of the water is high, further circulation of the water through the collector is useless. This is due to the low thermal conductivity of water of 0.6 W/m.K compared to metals which is many orders higher. Hence it is necessary to reduce the surface temperature either by pumping water at a higher flow rate or by enhancing the fluid’s properties by the dispersion of nanoparticles. Pumping water at higher flow rates is not advantageous as the overall efficiency of the system is lowered. Liquids in which nanosized particles of metal or their oxides are dispersed in a base liquid such as water are known as 'Nanofluids'. This results in higher values of thermal conductivity compared to the base liquid. The thermal conductivity increases with the concentration and temperature of the nanofluid. The increase in thermal conductivity with temperature is advantageous for application in collectors as the solar insolation varies throughout the day, with a minimum in the morning reaching a maximum at 2.00p.m and reducing thereafter. The efficiency of the collector estimated using a TiO2 nanofluid of 0.3% concentration is about 0.73, compared to water which is about 0.58. The efficiency is enhanced by 16.7% maximum with 30–50nm sized TiO2 nanoparticles dispersed in the water, compared to the system working solely with water. The flow rate is fixed at 2.7 liters per minute for both liquids.